2019
DOI: 10.1038/s41598-019-54470-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age and gender on the pulse waveform in optic nerve head circulation in healthy men and women

Abstract: The influences of age and gender differences on the pulse waveform in the optic nerve head (ONH) in healthy adults, using laser speckle flowgraphy (LSFG) were evaluated. We studied 908 healthy subjects (men = 701, age: 50.0 ± 9.1, women = 208, age: 49.8 ± 9.5, p = 0.76), evaluating these pulse waveform parameters: the blowout score (BOS), blowout time (BOT), acceleration time index (ATI), and the rising and falling rates. The parameters were analyzed separately for the tissue, vessels, and throughout the optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 34 publications
(56 reference statements)
5
13
0
Order By: Relevance
“…Thus, changes in the MT- or MV-RR will be correlated with changes in HR. Previous studies have reported that women have higher MT- 6 and MV-RR 17 compared to men 7 9 , which was consistent with the current result.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Thus, changes in the MT- or MV-RR will be correlated with changes in HR. Previous studies have reported that women have higher MT- 6 and MV-RR 17 compared to men 7 9 , which was consistent with the current result.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, MT- and MV-BOS showed a significant negative correlation with age and a positive correlation with DBP and HR in healthy participants (Table 4 ). These results suggest that the decrease in MT- or MV-BOS systemically reflects an age-related increase in the stiffness of large arteries, consistent with the previous results 6 , 17 , and are compatible with a very strong negative correlation of MT- or MV-BOS to the resistivity index (Spearman’s correlation coefficient: − 0.997– − 0.991). The opposite direction of correlation of MT- or MV-BOS to age and DBP may be explained as previously described for MT- or MV-Skew.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations